Primary ovarian small cell carcinoma of pulmonary type with coexisting endometrial carcinoma in a breast cancer patient receiving tamoxifen: A case report and literature review. Issue 23 (June 2018) - Yin, Lei; Li, Jianning; Wei, Yunhai; Ma, Dejian; Sun, Yamei; Sun, Yanlai
Abstract: Rationale: Small cell carcinoma of the ovary (SCCO) is a rare and aggressive extra-pulmonary variant of small cell tumors of uncertain histogenesis. The pathogenesis and optimal treatment of SCCO is unclear. We present a very rare case of a synchronous primary ovarian small cell carcinoma and endometrioid adenocarcinoma of the uterus in a patient after 2 years of tamoxifen treatment for breast cancer. This is the first such report in the English literature. Patient concerns: A 46-year-old woman had a history of left breast cancer that was treated with a simple mastectomy and sentinel lymph node biopsy in 2013. The post-operative pathology was invasive ductal carcinoma of the left breast. she had been taking tamoxifen for 2 years. The patient underwent an exploratory laparotomy to reduce the tumor burden, improve bowel compression symptoms, and promote defecation in 2015. The post-operative pathology revealed a rare, simultaneous occurrence of two tumors (endometrial adenocarcinoma and SCCO [pulmonary type]). Diagnoses: Primary ovarian small cell carcinoma of pulmonary type with coexisting endometrial carcinoma in a breast cancer patient. Interventions: The patient received 3 courses of chemotherapy after operation. The effect was not apparent and the general health status was poor. Outcomes: The patient died of progressive disease 7 months post-operatively. Lessons: The present case suggests that tamoxifen use might be among many etiologic factors in SCCO development. Despite its rarity, SCCO requires a high degree of attention in clinical work because it is an aggressive tumor that has a poor prognosis.